Political participation of Afro-Ecuadorian women in Esmeraldas, 2009-2021 - Espinoza, Jenniffer (2022)
This article analyzes the application of affirmative actions for the political participation of Afro-Ecuadorian women from the canton of Esmeraldas, from a human rights and gender perspective. To do this, the review of academic articles related to the right of participation and the ethnic-cultural identity of peoples and communities is carried out; in turn, of the pertinent legal and constitutional regulations, and of the statistical results of the 2009-2021 electoral period. Finally, the experiences of Afro-Ecuadorian women in electoral processes and how these women understand the right to political participation in society are incorporated.